2018
DOI: 10.4236/sm.2018.82006
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Job Orientation and Job Stress on Marital Adjustment among Guilan Office of Education Staff

Abstract: Family is a social unit, an organization, a group and also a small society that, in sociologists' view, is the first structured unit in a social system. A healthy society requires a healthy family and marital adjustment is one of its requirements. On this basis, this study aimed to identify the effect of job orientation and job stress on marital adjustment among Guilan Office of Education staff. Statistical population of this study was Guilan Office of Education staff in 2015 that 100 people were selected with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The research conducted by Lopez et al (2014) showed that increasing work pressure is related to decreasing JS and decreasing adaptability (Lopes, Lagoa, & Calapez, 2014). On the other hand, there is a significant positive relationship between E-ISSN: 2783-333X orientation and JS with satisfaction and MA (Batool, Hussain, & Bajwa, 2017;Dehghanmehr et al, 2016;Sadeghi, Khedmati, & Yousefi, 2018). Reviewing and reviewing the research literature shows a positive relationship between MI, SC, and JS with MA.…”
Section: Introductionmentioning
confidence: 99%
“…The research conducted by Lopez et al (2014) showed that increasing work pressure is related to decreasing JS and decreasing adaptability (Lopes, Lagoa, & Calapez, 2014). On the other hand, there is a significant positive relationship between E-ISSN: 2783-333X orientation and JS with satisfaction and MA (Batool, Hussain, & Bajwa, 2017;Dehghanmehr et al, 2016;Sadeghi, Khedmati, & Yousefi, 2018). Reviewing and reviewing the research literature shows a positive relationship between MI, SC, and JS with MA.…”
Section: Introductionmentioning
confidence: 99%